Effect of Zingiber officinale and propolis on microorganisms and endotoxins in root canals - MAEKAWA, Lilian Eiko (Faculdade de Odontologia de Bauru da Universidade de São Paulo, 2013)
The purpose of this study was to evaluate the effectiveness of glycolic propolis (PRO) and ginger (GIN) extracts, calcium hydroxide (CH), chlorhexidine (CLX) gel and their combinations as ICMs (ICMs) against Candida albicans, Enterococcus faecalis, Escherichia coli and endotoxins in root canals. MATERIAL AND METHODS: After 28 days of contamination with microorganisms, the canals were instrumented and then divided according to the ICM: CH+saline; CLX, CH+CLX, PRO, PRO+CH; GIN; GIN+CH; saline. The antimicrobial activity and quantification of endotoxins by the chromogenic test of Limulus amebocyte lysate were evaluated after contamination and instrumentation at 14 days of ICM application and 7 days after ICM removal. RESULTS AND CONCLUSION: After analysis of results and application of the Kruskal-Wallis and Dunn statistical tests at 5% significance level, it was concluded that all ICMs were able to eliminate the microorganisms in the root canals and reduce their amount of endotoxins; however, CH was more effective in neutralizing endotoxins and less effective against C. albicans and E. faecalis, requiring the use of medication combinations to obtain higher success.